Food Allergies: New Evidence for Peanut Introduction. Issue 3 (May 2016) - Morin, Karen H.
Abstract : Approximately 15 million Americans have food allergies, 8% of which are children. Food allergies are therefore a major public health issue. New guidelines suggest introducing peanuts early in the diet of children who are high risk for developing peanut allergies. Our nutrition expert, Dr. Morin, provides an update.